KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI PROFESIONAL GURU DI SMA - Yulia Purnama Sari (UNIVERSITAS BENGKULU, 2015)
The role of headmaster’s leadership in increasing teachers’ professional competence was mainly discussed in this research. The descriptive qualitative method was used in this researchinvolving the headmaster, the teachers, and the staff. The result showed that the role of headmaster’s leadership (1) as administrator, was done by sharing responsibility of learning to theteachers; (2) as supervisor by: considering the teaching distribution duty carefully; (3) as manager by: finishing the school program together, (4) as motivator by: building comfortable environment for teaching and leraning.Keyword: headmaster, teacher, professional competence